Whither rice health in the lowlands of Asia: Shifts in production situations, injury profiles, and yields - Savary, Serge; Willocquet, Laetitia; Castilla, Nancy; Nelson, Andy; Shankar Singh, Uma; Kumar, Jatinder; Teng, Paul S. (Wiley, 2022)
Emphasizing connectedness among the many elements of plant‐based systems that are collectively addressed in One Health is a logical outcome of debates generated by the International Year of Plant Health. The notion of One Health was implemented through the joint use of the concepts of production situation (PS)—the “rice way of life”—and injury profile (IP)—rice health (pathogens, animal pests, and weeds)—in a population of 1051 rice farmers’ fields surveyed from 1987 to 2011. Seven associated PSs and nine IPs are characterized. An ending Green Revolution (Period 1) and a post‐Green Revolution (Period 2) are considered. Major changes in PSs and IPs occurred, with increased mineral fertilizer inputs, pesticide applications, and landscape uniformity, along with shortening fallow periods, and dropping labour. Increases or decreases in some injuries lead to shifts in IPs towards more frequent bacterial, flower, and panicle diseases. Yield gain between the two periods was marginal but yield losses to IPs remained unchanged. Yet there was an increase by 77.0%, 21.6%, and 439% for insecticides, herbicides, and fungicides, respectively, along with a 27.9% increase in mineral fertilizer inputs. Total factor productivity in rice production dropped by over 40% during the 24 intervening years, not accounting for the long‐term effects of these changes on soil fertility, biodiversity, and scarcer water resource. These results call for urgently required reassessment of public efforts to safeguard these agrosystems that are of critical importance economically, socially, and culturally for roughly half the world's population.